The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-1-4939-3387-7_33
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of Transgenic Rodent Parasites for the Preclinical Evaluation of Malaria Vaccines

Abstract: Rodent transgenic parasites are useful tools for the preclinical evaluation of malaria vaccines. Over the last decade, several studies have reported the development of transgenic rodent parasites expressing P. falciparum antigens for the assessment of vaccine-induced immune responses, which traditionally have been limited to in vitro assays. However, the genetic manipulation of rodent Plasmodium species can have detrimental effects on the parasite's infectivity and development. In this chapter, we present a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Pioneering studies reported the use of rodent malaria parasites to investigate the functional relevance of P. falciparum liver stage [79] and blood stage [58] vaccine candidates. Most of the recently developed P. berghei chimeras have been accomplished using the twostep gene insertion marker out technique [80], which has been used in assessing both transmission-blocking [81] and pre-erythrocytic vaccines [82,83], enabling successful replacement of orthologous gene targets and also marker-free parasite lines. More recently, Shinzawa and colleagues developed a transgenic P. berghei line constitutively expressing the Sp-Cas9 gene [84], which could be of great interest for future work involving P. berghei as a model.…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…Pioneering studies reported the use of rodent malaria parasites to investigate the functional relevance of P. falciparum liver stage [79] and blood stage [58] vaccine candidates. Most of the recently developed P. berghei chimeras have been accomplished using the twostep gene insertion marker out technique [80], which has been used in assessing both transmission-blocking [81] and pre-erythrocytic vaccines [82,83], enabling successful replacement of orthologous gene targets and also marker-free parasite lines. More recently, Shinzawa and colleagues developed a transgenic P. berghei line constitutively expressing the Sp-Cas9 gene [84], which could be of great interest for future work involving P. berghei as a model.…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…These models allow the use of mice for testing novel CSP-based vaccine candidates, such as a self-assembling protein nanoparticlebased malaria vaccine [9], or monoclonal antibodies binding to the vaccine antigen [10], potentially defining new protective epitopes. Specific chimeras can be engineered to study other antigens, such as TRAP or CelTOS, and guidelines have been published [11].…”
Section: Development Of Challenge Strainsmentioning
confidence: 99%
“…This prevents malaria disease caused by asexual parasite blood stages and further transmission mediated by sexual blood stages. Moreover, genetically (GAP) and chemically attenuated (CAP) P. falciparum and rodent malaria parasites have con rmed the protective e cacy of whole attenuated parasites [16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%